Planning and governance for green transformation of the Yellow River Basin: an analytical framework for green evaluation and governance in resource-based cities - Zhang, Hang; Chen, Xingpeng (Frontiers in Environmental Science, 2026)
The green transformation of national spatial planning is a critical pathway to global sustainable development. Existing research has examined sector-specific strategies, but the role of integrated spatial planning as an institutional driver of urban sustainability remains underexplored. This study focuses on resource-based cities in China’s Yellow River Basin. It develops a spatial-planning-oriented analytical framework aligned with the Sustainable Development Goals (SDGs) to assess green transformation dynamics. Using a panel dataset for 36 cities from 2006 to 2020, we use entropy weighting, coupling coordination modelling, kernel density estimation and grey relational analysis to evaluate transformation performance, spatial and temporal evolution and key influencing factors. The results show three main findings. Comprehensive green transformation levels improve markedly, and the coupling coordination degree shifts from moderate to relatively high coordination. Transformation levels display a clear spatial clustering pattern characterised by “east leading, centre rising and west catching up”. The urbanisation rate, per capita GDP and fiscal expenditure act as dominant drivers, while technological innovation has a weaker but still positive effect. The study highlights the need to embed differentiated governance strategies within the national spatial planning system. It also offers targeted recommendations on planning hierarchy, policy integration and technical standards to support a coordinated green transition in resource-intensive regions.